Investigation of smoke-taint precursor modification by glycosidase activity in diverse wine yeast and bacterial strains - Piao, Hailan; Collins, Thomas S.; Henick-Kling, Thomas (Frontiers in Microbiology, 2025)
The increasing prevalence of wildfires presents a growing risk to wine production through the development of smoke-taint, a sensory defect in wine caused by volatile phenols absorbed by grapevines during smoke exposure. In grapes and wine, these volatile phenols are often present in glycosylated forms that can be hydrolyzed during fermentation, releasing undesirable smoky aromas. This study investigated the glycosidase activity of diverse Saccharomyces cerevisiae and Oenococcus oeni strains to evaluate their roles in modulating smoke-taint-associated glycosides during wine fermentation. Mini-scale alcoholic and malolactic fermentations were conducted in synthetic media enriched with flavor extracts from smoke-exposed grapes using reverse osmosis. LC–MS profiling revealed strain-dependent hydrolysis of glycosides, linked to smoke-taint. Notably, S. cerevisiae strains UCD514 and UCD525, and O. oeni strain UCD199, showed the highest glycosidase activity. Principal component analysis further confirmed that individual microbial strains had distinct metabolic impacts on glycoside profiles. This study highlights a wide range of glycosides that can be hydrolyzed by wine yeast and bacteria. These findings demonstrate the dual potential of microbial glycosidase activity to mitigate smoke-taint while enhancing wine aroma. In addition, the results help distinguish smoke-taint-associated glycosides that are resistant to microbial hydrolysis from those that are readily cleaved, enabling targeted removal of released aroma compounds through downstream filtration approaches.